1980
DOI: 10.1113/jphysiol.1980.sp013319
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory noradrenergic and serotonergic pathways to hypothalamic units

Abstract: SUMMARY1. In guinea-pigs hypothalamic single units were extracellularly tested for their response to thermal stimulation of the skin and to electrical stimulation of two different pontine areas, the nucleus raph6 magnus and the dorsomedial reticular formation. Furthermore, thermoregulatory control actions were measured during the stimulations.2. Electrical stimulation of those reticular formation areas containing noradrenaline cells caused an increase of oxygen uptake, electrical muscle activity and body tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…28 The involvement of NE in central thermoregulation and the etiology of hot flushes are supported by results from experimental and animal studies that showed that increased central nervous system levels of NE narrows the width of the thermoneutral zone. 29,30 This is consistent with results from studies that showed that yohimbine, an ␣ 2 -adrenergic antagonist, elevates brain NE 31 and ultimately triggers hot flushes. 32 Thus, ␣ 2 -adrenoceptors in the hypothalamus may be responsible for the events of the hot flush.…”
Section: Discussionsupporting
confidence: 79%
“…28 The involvement of NE in central thermoregulation and the etiology of hot flushes are supported by results from experimental and animal studies that showed that increased central nervous system levels of NE narrows the width of the thermoneutral zone. 29,30 This is consistent with results from studies that showed that yohimbine, an ␣ 2 -adrenergic antagonist, elevates brain NE 31 and ultimately triggers hot flushes. 32 Thus, ␣ 2 -adrenoceptors in the hypothalamus may be responsible for the events of the hot flush.…”
Section: Discussionsupporting
confidence: 79%
“…Comparing the present results with those reported earlier, the more intense labeling of the RMg in the SF and IF groups appears to reflect a rise in body temperature or a change in respiratory pattern due to somatic and autonomic movements in the groups presenting a more intense motor activity (6,8). The more intense labeling of the RPa seems to emphasize its reported role as a pre-motor nucleus in somatic and autonomic motor events, particularly regarding mastication, swallowing and gastrointestinal contractility as well as gastric secretion through the vagal complex (6,10,13).…”
supporting
confidence: 62%
“…Among such structures in the brainstem are the caudal raphe nuclei, namely the raphe magnus (RMg), pallidus (RPa) and obscurus (ROb) nuclei. This view is corroborated by the following anatomical and physiological data: the RMg has been related mainly to analgesia, but together with the RPa it also seems to be involved in the regulation of respiratory frequency and body temperature (7,8). The RPa projects to the facial, hypoglossus, ambiguous and trigeminal motor nuclei (9,10).…”
supporting
confidence: 60%
“…Second, 5-HT is well known to suppress appetite, most probably via hypothalamic projections (see Curson, 1990). Third, a number of lines of evidence have implicated the raphe and 5-HT in thermoregulation, including (1) the presence ofthermosensitive neurons in the rostra1 raphe (Cronin and Baker, 1976;Hori and Harada, 1976); (2) enhanced firing of neurons in the preoptic area of the hypothalamus following rostra1 raphe stimulation (Bruck and Hinckel, 1980;Werner and Bienek, 1985) and (3) abolition of the thermoresponsiveness of preoptic neurons following lesions of the rostra1 raphe (Taylor, 1982;Werner and Bienek, 1985). Interestingly, the fever induced by administering bacterial pyrogens may be attenuated by raphe lesions (Kadlecova et al, 1977) or by depleting (Harvey and Milton, 1974;Kandasamy, 1977;Matuszek and Ishikawa, 198 1) or antagonizing (Kandasamy, 1977) central 5-HT (see Myers, 1980).…”
Section: Discussionmentioning
confidence: 99%